Associations between visual perception accuracy and confidence in a dopaminergic manipulation study - Andreou, Christina; Bozikas, Vasilis P.; Luedtke, Thies; Moritz, Steffen (Frontiers in Psychology, 2015)
Delusions are defined as fixed erroneous beliefs that are based on misinterpretation of events or perception, and cannot be corrected by argumentation to the opposite. Cognitive theories of delusions regard this symptom as resulting from specific distorted thinking styles that lead to biased integration and interpretation of perceived stimuli (i.e., reasoning biases). In previous studies, we were able to show that one of these reasoning biases, overconfidence in errors, can be modulated by drugs that act on the dopamine system, a major neurotransmitter system implicated in the pathogenesis of delusions and other psychotic symptoms. Another processing domain suggested to involve the dopamine system and to be abnormal in psychotic disorders is sensory perception. The present study aimed to investigate whether (lower-order) sensory perception and (higher-order) overconfidence in errors are similarly affected by dopaminergic modulation in healthy subjects. Thirty-four healthy individuals were assessed upon administration of L-dopa, placebo, or haloperidol within a randomized, double-blind, cross-over design. Variables of interest were hits and false alarms in an illusory perception paradigm requiring speeded detection of pictures over a noisy background, and subjective confidence ratings for correct and incorrect responses. There was a significant linear increase of false alarm rates from haloperidol to placebo to L-dopa, whereas hit rates were not affected by dopaminergic manipulation. As hypothesized, confidence in error responses was significantly higher with L-dopa compared to placebo. Moreover, confidence in erroneous responses significantly correlated with false alarm rates. These findings suggest that overconfidence in errors and aberrant sensory processing might be both interdependent and related to dopaminergic transmission abnormalities in patients with psychosis.